Prenatal Yoga untuk Mengatasi Ketidaknyamanan pada Ibu Hamil Puskesmas Lerep - Mega Nasanova; Rini Susanti; Via Muafifah; Alvin Nurul Jannah (Prosiding Seminar Nasional dan CFP Kebidanan Universitas Ngudi Waluyo, 2022)
Yoga is a way of preparation that focuses on muscle control, breathing techniques, relaxation and peace of mind. Relaxation techniques can be done by imagining something pleasant that can make the body relax. Prenatal yoga that is done regularly can create physical health, bring peace of mind and mind. Practicing yoga and meditation regularly during pregnancy will establish harmonious communication between the mother-to-be and her baby. Physical changes that occur during pregnancy will affect an uncomfortable pregnancy, so the mother feels anxiety during pregnancy. Practicing yoga at this time is a useful solution as a medium of self-help that will reduce discomfort/anxiety during pregnancy. The problem in this study is the lack of interest of pregnant women to do prenatal yoga and knowledge of pregnant women about prenatal yoga because pregnant women have never done prenatal yoga. The solution to this problem is to conduct counseling about prenatal yoga and practice the steps of prenatal yoga.used is a demonstration about prenatal yoga and giving a questionnaire to determine the level of knowledge of pregnant women. There were 10 pregnant women who were invited but only 8 people came. The implementation date of the service is on June 5, 2022 at 09.00-Finished. of this service indicate that 6 people have good knowledge (75%), 1 person has sufficient knowledge (12.5%), and 1 person has less knowledge (12.5%). AbstrakPrenatal yoga yang dilakukan secara teratur dapat menciptakan kesehatan fisik, menghadirkan ketenangan dalam pikiran dan batin. Berlatih yoga dan meditasi secara teratur pada masa hamil akan menjalin komunikasi yang harmonis antara calon ibu dan buah hatinya. Perubahan fisik yang terjadi selama hamil akan memengaruhi kehamilan yang tidak nyaman, sehingga ibu merasa kecemasan dalam menjalani kehamilan. Berlatih yoga pada masa ini merupakan salah satu solusi yang bermanfaat sebagai media self help yang akanmengurangi ketidaknyamanan/ kecemasan selama hamil.. yang digunakan adalah dengan demostrasi tentang prenatal yoga dan memberikan kuesioner untuk mengetahui tingkat pengetahuan ibu hamil. Ibu hamil yang di undang ada 10 orang tetapi yang datang hanya 8 orang. Tanggal pelaksanaan pengabdian yaitu pada tanggal 05 Juni 2022 jam 09.00-Selesai. pengabdian ini menunjukkan bahwa ibu yang berpengetahuan baik sebanyk 6 orang (75%), pengetahuan cukup sebanyak 1 orang (12,5%), dan pengetahuan kurang sebanyak 1 orang (12,5%).